Diversity and Bionomics of Sandflies (Diptera: Psychodidae) of an Endemic Focus of Cutaneous Leishmaniasis in Zagora Province, Southeast of Morocco - Al-Koleeby, Zalalham (J Parasitol Res, 2021)
The diversity and seasonality for sandflies were studied in 2019 at a focus of zoonotic cutaneous leishmaniasis in Zagora province, southern Morocco. Standardized sampling with CDC light traps was used. A total of 4504 sandflies (4024 Phlebotomus and 480 Sergentomyia) was collected during the study period. Seven species belonging to genus Phlebotomus and six species of genus Sergentomyia were identified. The most abundant species were Ph. papatasi (33.6%) and Ph. longicuspis (25.7%), highlighting the risk for local disease transmission foci. The seasonal activity of sandflies extended from April to November, showing two peaks, one in June-July and one, less important, in late-September-October. Abundance was highest during the months May, June, and July and lowest in August, September, and October. Results of this study provide important baseline data for planning control interventions.